2005
DOI: 10.1016/j.biosystems.2004.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions promote synchronous activities in a network of inhibitory interneurons

Abstract: By using a single compartment biophysical model of a fast spiking interneuron the synchronization properties of a pair of cells, coupled by electrical and inhibitory synapses, are investigated. The inhibitory and excitatory synaptic couplings are modeled in order to reproduce the experimental time course of the corresponding currents. It is shown that increasing the conductance value of the electrical synapses enhances the synchronization between the spike trains of the two cells. Moreover, increasing either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…In the FS cell model, the dependence of phase locking on intrinsic frequency is qualitatively the same as that seen in integrate-and-fire models (Chow and Kopell, 2000;Lewis, 2003;Lewis and Rinzel, 2003;Pfeuty et al, 2003) and in other conductance-based models (Nomura et al, 2003;Pfeuty et al, 2003;Di Garbo et al, 2005).…”
Section: Experimentally Determined Prcs Predict Only Synchronous Actisupporting
confidence: 59%
See 1 more Smart Citation
“…In the FS cell model, the dependence of phase locking on intrinsic frequency is qualitatively the same as that seen in integrate-and-fire models (Chow and Kopell, 2000;Lewis, 2003;Lewis and Rinzel, 2003;Pfeuty et al, 2003) and in other conductance-based models (Nomura et al, 2003;Pfeuty et al, 2003;Di Garbo et al, 2005).…”
Section: Experimentally Determined Prcs Predict Only Synchronous Actisupporting
confidence: 59%
“…Recent theoretical work has suggested that the ability of electrical coupling to synchronize the activity of cells depends on a number of factors, including coupling strength and firing frequency (Chow and Kopell, 2000;Lewis and Rinzel, 2003;Nomura et al, 2003;Pfeuty et al, 2003;Di Garbo et al, 2005;Bem et al, 2005;Saraga et al, 2006). This theoretical work predicts that, under most conditions, electrical synapses promote synchronous activity, but they can also support antiphase activity between coupled neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, magnetoencephalography (MEG), a functional neuroimaging technique, is used for mapping brain activity. The signals measured in EEG and MEG can be decomposed into distinct frequency bands such as 1-3 Hz (delta), 4-7 Hz (theta), [8][9][10][11][12][13][14][15] Hz (alpha), 16-31 Hz (beta), and 32-70 Hz (gamma). There is a correlation between these rhythms and behaviors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the dynamic behavior of a network has attracted much attention in recent years [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Gibson et al [6] showed by paired-cell recordings that while the same type of inhibitory neurons were strongly interconnected by electrical synapses, electrical synapses between different inhibitory cell types were rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation